CMOS integrated image sensor - Ye, Dajun. (2008)
This project studies the photodiodes and their integration to form APS for imaging application. APS cells with different structures were simulated and fabricated using in-house NTU 2?m Nwell CMOS technology. The performance of the fabricated photodiodes and integrated-mode and logarithmic-mode APS cells were characterized on wafer level.